Phenotyping open-pollinated maize varieties for environments with low nitrogen availability - do Amaral, Camila Baptista [UNESP] (2018)
The high nitrogen nutrient requirement of maize is a major production constraint in areas that have a low availability of soil nitrogen. A 2-year field experiment was conducted to characterize open-pollinated varieties of maize by identifying possible sources of variability targeting low N environments. Twelve experimental varieties and two checks, AL Avaré and Ipanema, were cultivated under high and low nitrogen levels and evaluated for chlorophyll content index, lodging, prolificacy and grain yield. The results indicate that the applied nitrogen resulted in differences in the chlorophyll content index between environments. Nitrogen level affected the percentage of lodged plants of varieties K and L. Grain yield and lodging were the traits that most affected genotypic variability, and 17% of the studied varieties were considered as superior due to higher lodging-resistance and higher grain yield.